1979
DOI: 10.1108/eb026682
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Type of Sources Used on the Results of Citation Analyses

Abstract: Most citation analyses are based on references taken from two or three source journals. There are good theoretical reasons for believing that these may not be representative of all references. In the social science citation analyses carried out as part of the DISISS programme, references were collected from 140 journals, including forty‐seven drawn at random from a comprehensive list, and also from 148 monographs. Analyses of references drawn from high ranking and randomly selected journals showed differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 2 publications
0
12
0
5
Order By: Relevance
“…Line (1979) obtained similar findings for references contained in journals and monographs in social sciences and alluded to the fact that "monographs may be used as a vehicle for new knowledge in the social sciences" (p. 282), which is equally applicable to monographs in the arts and humanities. Yet ISI treats non-journal sources cited in the arts and humanities journal articles somewhat differently and considers more than 70% of them as "noncitable" items ( "noncitable" items constitute 22% of all items in SCI and 46% in SSCI) (Jacsó, 2001, p. 591).…”
Section: Discussionmentioning
confidence: 60%
“…Line (1979) obtained similar findings for references contained in journals and monographs in social sciences and alluded to the fact that "monographs may be used as a vehicle for new knowledge in the social sciences" (p. 282), which is equally applicable to monographs in the arts and humanities. Yet ISI treats non-journal sources cited in the arts and humanities journal articles somewhat differently and considers more than 70% of them as "noncitable" items ( "noncitable" items constitute 22% of all items in SCI and 46% in SSCI) (Jacsó, 2001, p. 591).…”
Section: Discussionmentioning
confidence: 60%
“…There are numerous studies of the characteristics of social science information and the information-seeking activities of social scientists, both academic and nonacademic (e.g., Ellis, 1989Ellis, , 1993Ellis, Cox, & Hall, 1993;Garvey, Lin, & Nelson, 1970, 1971Line, 1971Line, , 1973Line, , 1979Line, , 1981Line, Brittain, & Cranmer, 1971). These and other more recent studies have, in turn, been extensively reviewed (e.g., Adam, 1982;Eager & Oppenheim, 1996;Ellis, 1986;Hogeweg de Haart, 1983a, 1983bPreschel & Woods, 1989).…”
Section: Information-seeking Behavior: Social Scientistsmentioning
confidence: 99%
“…Several empirical studies have shown that there is li le correlation between the citation patterns to monographic literature and those of journal literature. 1 Researchers further indicate that one of the limitations of citation databases produced by the Institute of Scientific Information (ISI) is that they are oriented almost exclusively to citations in journal publications. Consequently, warnings have been issued against blindly using the ISI citation data.…”
mentioning
confidence: 99%